RPFdb v2.0: an updated database for genome-wide information of translated mRNA generated from ribosome profiling - Wang, Hongwei (Nucleic Acids Res, 2019)
RPFdb (http://www.rpfdb.org or http://sysbio.sysu.edu.cn/rpfdb) is a public database for hosting, analyzing and visualizing ribosome profiling (ribo-seq) data. Since its initial release in 2015, the amount of new ribo-seq data has been considerably enlarged with the increasing popularity of ribo-seq technique. Here, we describe an updated version, RPFdb v2.0, which brings significant data expansion, feature improvements, and functionality optimization: (i) RPFdb v2.0 currently hosts 2884 ribo-seq datasets from 293 studies, covering 29 different species, in comparison with 777 datasets from 82 studies and 8 species in the previous version; (ii) A refined analysis pipeline with multi-step quality controls has been applied to improve the pre-processing and alignment of ribo-seq data; (iii) New functional modules have been added to provide actively translated open reading frames (ORFs) information for each ribo-seq data; (iv) More features have been made available to increase database usability. With these additions and enhancements, RPFdb v2.0 will represent a more valuable and comprehensive database for the gene regulation community.